Iron Catalyzed Aminohydroxylation of Olefins - Williamson, Kevin S. (2010)
[Image: see text] We have discovered that N-sulfonyl oxaziridines react with a broad range of olefins in the presence of iron salts to afford 1,3-oxazolidines. This process provides access to 1,2-aminoalcohols with the opposite sense of regioselectivity produced from the copper-catalyzed oxyamination previously reported from our labs. Thus, either regioisomeric form of 1,2-aminoalcohols can easily be obtained from the reaction of oxaziridines with olefins, and the sense of regioselectivity can be controlled by the appropriate choice of inexpensive, non-toxic first row transition metal catalyst.